FUT2 secretor status is not associated with oral poliovirus vaccine immunogenicity in south Indian infants - Parker,EPK; Whitfield,H; Baskar,C; Giri,S; John,J; Grassly,N; Kang,G; Praharaj,I (Journal of Infectious Diseases, 2019)
FUT2 determines whether histo-blood group antigens are secreted at mucosal surfaces. Secretor status influences susceptibility to enteric viruses, potentially including oral poliovirus vaccine (OPV). We performed a nested case–control study to determine the association between FUT2 genotype (single-nucleotide polymorphisms G428A, C302T, and A385T) and seroconversion among Indian infants who received a single dose of monovalent type 3 OPV. Secretor prevalence was 75% (89 of 118) in infants who seroconverted and 80% (97 of 122) in infants who did not seroconvert (odds ratio, 0.79; 95% confidence interval, .43–1.45). Our findings suggest that FUT2 genotype is not a key determinant of variation in OPV immunogenicity.